You are not your data. (27th July 2018) - Pennycook, Gordon
Abstract: Scientists should, above all else, value the truth. To do this effectively, scientists should separate their identities from the data they produce. It will be easier to make replications mainstream if scientists are rewarded based on their stance toward the truth – such as when a scientist reacts positively to a failure to replicate – as opposed to a particular finding.